Інженерний менеджмент для підвищення надійності електропостачання - Трунова, І. М.; Середа, А. І.; Дудніков, С. М.; Пазій, В. Г.; Мороз, О. М.; Савченко, О. А.; Попадченко, С. А.; Галько, Сергій Віталійович; Ладижинський, І. В.; Trunova, І.; Sereda, A.; Dudnikov, S.; et al. (Запоріжжя : 2024, 2024)
UA: Запропоновані рекомендації щодо інженерного менеджменту на прикладі бізнес-аналізу проекту автоматизованої системи контролю якості технічної експлуатації розподільних мереж. Визначені вимоги державних органів регулювання та контролю, на основі яких формуються певні бази звітних даних Операторів систем розподілу, що можуть бути інтегровані до автоматизованої системи контролю якості технічної експлуатації розподільних мереж. Визначені цілі та очікувані результати від впровадження автоматизованої системи контролю якості технічної експлуатації розподільних мереж та обґрунтована функціональна декомпозиція задач проекту. Розроблена блок-схема економічного обґрунтування реконструкції повітряної лінії електропередачі з використанням бази даних економічних витрат попереднього року перед реконструкцією. EN: Recommendations for the use of one of the tools of engineering management - business analysis are proposed. An example of business analysis of the project of an automated quality control system for the technical operation of energy equipment of distribution systems is given. The requirements of state regulatory and control bodies (the National Commission for State Regulation in the Fields of Energy and Utilities and the State Inspectorate for Energy Supervision) are defined, based on which certain reporting databases of distribution system operators are formed, which can be integrated into the automated quality control system of technical operation of energy equipment. The goals and expected results from the implementation of the automated quality control system for the technical operation of distribution networks are defined. A well-founded functional decomposition of the tasks of the project of the automated system of quality control of the technical operation of distribution networks, namely, the phases of project initiation, planning, execution of the main works of the project, control of results and completion of the project. The main components of the processes of installation and configuration of equipment and software, monitoring and analysis of results, the main interfaces of the automated quality control system of the technical operation of distribution networks are defined. A block diagram of the economic justification of the reconstruction of the overhead power line using the database of economic costs of the previous year before the reconstruction was developed. It was concluded that the proposed stages of the preliminary comprehensive business analysis of the project of the automated quality control system of the technical operation of the energy equipment of distribution systems are the basis for its successful implementation to increase the reliability of electricity supply. The proposed stages of the preliminary comprehensive business analysis of the project of the automated quality control system of the technical operation of the energy equipment of distribution systems are the basis for its successful implementation to increase the reliability of electricity supply. A flowchart of an example of income calculations for the economic justification of the reconstruction of the PL based on the use of the databases of the previous year before the reconstruction can also be useful for this purpose.
Engineering management to increase the power supply continuity
Keywords: розподільна мережа електропостачання; автоматизована система; контроль якості; технічна експлуатація; інженерний менеджмент; бізнес-аналіз; power distribution network; automated system; quality control; technical operation; business analysis